Analysis of the Implementation of the Village Financial System Application (SISKEUDES) in Village Financial Management: A Case Study of Sidamulya Village, Wanasari District, Brebes Regency - Nurul Mahmudah; Yusri Anis Faidah; Cantika Putri Cahaya Purnama (Jurnal Ekonomi, 2025)
This study aims to analyze the implementation of the Village Financial System Application (SISKEUDES) in village financial management, with a case study conducted in Sidamulya Village, Wanasari District, Brebes Regency. This research employs a qualitative method using both primary and secondary data sources. Primary data were obtained through interviews with key informants, including the Village Head of Sidamulya, the Village Secretary, and the Finance Officer who also serves as the SISKEUDES administrator. Secondary data consisted of government regulations, laws, books, modules, and journals related to village financial management and the use of SISKEUDES, as well as SISKEUDES input documents such as the Village Medium-Term Development Plan, the Village Government Work Plan, village revenue and expenditure budget data, financial administration reports, and bookkeeping records. Data collection techniques included observation, documentation, and direct interviews, while data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of this study indicate that village financial management in Sidamulya Village has been carried out in accordance with the principles of transparency, accountability, participation, orderliness, and budgetary discipline as outlined in Minister of Home Affairs Regulation No. 20 of 2018. The implementation of SISKEUDES in Sidamulya Village has facilitated the work of local human resources, making supervision more efficient and ensuring compliance with applicable regulations, thereby increasing transparency and accountability. Moreover, SISKEUDES has played a significant role in developing the village’s accounting information system, particularly in terms of system quality and information quality, which are reflected through several indicators that demonstrate its effectiveness in supporting financial reporting in the village.